2017
DOI: 10.1016/j.jff.2017.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Stability and biological activity of Merlot (Vitis vinifera) grape pomace phytochemicals after simulated in vitro gastrointestinal digestion and colonic fermentation

Abstract: a b s t r a c tGrape pomace is an abundant/accessible food industry by-product that contains a wide range of phenolic compounds, which have been related to several health benefits and bioactivities. The aim of this study was to mimic the gastrointestinal digestion and the colonic fermentation of Merlot grape pomace, in order to unravel possible phytochemical contents reductions and the processes associated with them, as a tentative to relate the phenolic compound profiles of the extracts with their biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 37 publications
2
31
0
2
Order By: Relevance
“…Interestingly, the fermented rosemary extract exhibited a considerable cytotoxic activity (GI 50 = 116 µg/mL) against one of the cancer cell lines, namely the HeLa (cervical carcinoma). Corrêa, Haminiuk et al (2017), when analysing grape pomace preparations, reported a similar trend: the crude and digested extracts presented no antiproliferative effects against the same cell lines herein assessed. The corresponding grape pomace fermented extract displayed antiproliferative activity against all tumor cells, with a GI 50 value of 251 µg/mL against HeLa cells.…”
Section: Cytotoxic Propertiessupporting
confidence: 58%
See 2 more Smart Citations
“…Interestingly, the fermented rosemary extract exhibited a considerable cytotoxic activity (GI 50 = 116 µg/mL) against one of the cancer cell lines, namely the HeLa (cervical carcinoma). Corrêa, Haminiuk et al (2017), when analysing grape pomace preparations, reported a similar trend: the crude and digested extracts presented no antiproliferative effects against the same cell lines herein assessed. The corresponding grape pomace fermented extract displayed antiproliferative activity against all tumor cells, with a GI 50 value of 251 µg/mL against HeLa cells.…”
Section: Cytotoxic Propertiessupporting
confidence: 58%
“…Correa, Gonçalves et al (2017), when assessing the antioxidant activity of mate beverages using the same set of techniques, reported that the in vitro digestion and fermentation processes caused a decrease in the antioxidant capabilities of their samples, except for the ABTS assay. Corrêa, Haminiuk et al (2017), on their turn, found that the digestion step did not cause such impacts on a grape pomace hydroalcoholic The results are presented as mean ± SD. In each line different letters mean significant statistical differences (p < 0.05).…”
Section: Antioxidant Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…The MIC values reveal that the A. blazei ergosterol rich extract displayed excellent bacteriostatic effects against all tested bacteria, and also presented considerable bactericidal potential against these microorganisms, being especially potent against Enterobacter cloacae and Salmonella enteritidis (MBC values of 0.05 mg mL According to their MIC values, natural products can be considered strong inhibitors (MIC below 0.5 mg mL −1 ), moderate inhibitors (MIC between 0.6 and 1.5 mg mL −1 ), and weak inhibitors (MIC above 1.6 mg mL −1 ). 32,36 Thus, based on these parameters, the herein investigated A. blazei ergosterol rich extract can be classified as a strong inhibitor against all bacteria assessed. Moreover, the A. blazei extract was more effective than the antibiotic ampicillin at inhibiting all the tested bacteria, while it was more potent than streptomycin against M. flavus, E. cloacae, S. enteritidis and S. typhimurium.…”
Section: Bioactive Properties Of the A Blazei Extract Rich In Ergostmentioning
confidence: 99%
“…Standard curves were constructed with trolox (r 2 = 0.99) and the results were expressed as mmol trolox equivalents (TE)/mg lyophilisate material. The DPPH and the ABTS assays were conducted as described previously [25]. The lyophilisate concentrations (mg/mL) providing 50% antioxidant activity were calculated from the graphs of antioxidant activity against the sample concentrations.…”
Section: Biological Activities 261 Antioxidant Activity Evaluationmentioning
confidence: 99%